Development of the Markov moment problem approach in the optimal control theory - Sklyar, G. M.; Ignatovich, S. Yu. (Methods of Functional Analysis and Topology, 2007)
The paper is a survey of the main ideas and results on using of the Markov moment problem method in the optimal control theory. It contains a version of the presentation of the Markov moment approach to the time-optimal control theory, linear and nonlinear.